Transforming growth factor ββ1 expression in uterine leiomyomas and adjacent myometrium. Issue 2 (1st November 2004) - Sourla, Antigone; Gaka, Ioanna; Lembessis, Peter; Michalas, Stelios; Creatsas, George; Koutsilieris, Michael
Objective: To analyze the expression of transforming growth factor (TGF)ββ1 in human uterine leiomyomas and adjacent myometrium obtained at hysterectomy of women at mid/late follicular phase (n = 15), at mid/late luteal phase (n = 12) and after sex steroid ablation therapy. Materials and methods: Sex steroid ablation therapy was carried out using luteinizing-hormone-releasing hormone analog (triptorelin 3.75 mg intramuscularly every 28 days for at least 3 months; n = 10) and postmenopause (n = 8). The expression of TGFββ1 mRNA was analyzed by northern blots and in situ hybridization analysis while the immunohistochemical analysis assessed TGFββ1 expression at protein levels. In addition, we tested the time- and dose-dependent effects of TGFββ1 (0.5––50 ng/ml; final concentration; 24 and 48 h) on the proliferation (cell number; trypan blue exclusion) of KW smooth muscle-like myometrial cells in vitro. Results: Our data demonstrated that TGFββ1 (mRNA and protein) expression was higher in leiomyomas at mid/late follicular phase compared with those at luteal phase and to adjacent myometrium at either phases of the menstrual cycle. However, TGFββ1 expression (mRNA and protein) did not differ significantly among leiomyomas at luteal phase, leiomyomas after luteinizing-hormone-releasing hormone analog therapy, myometrium at follicular phase, myometrium at luteal phase and myometrium postmenopause. Conclusion: We conclude that TGFββ1 may be an important autocrine/paracrine factor in human leiomyomas particularly during the mid/late follicular phase.